School principal’s transformative leadership through increasing teacher’s pedagogical competence towards quality education - Muhib Ainul Yaqin (Institute of Computer Science (IOCS), 2023)
Increasing teacher pedagogic competence has a significant impact and contribution on the quality of education. Principal’s transformative leadership has an important role in the process. Therefore, this study aimed to reveal how the principal's leadership contributes to developing strategies to improve teacher pedagogical competence and to describe the model and realization of increasing teacher pedagogic competence. Through a qualitative approach, this research was conducted at Al-Furqon Junior High School Bondowoso. The results showed that there are several models of increasing teacher pedagogic competence that had been implemented. The model for increasing teacher pedagogic competence includes training and workshops, coaching and mentoring, reflection and self-assessment, development of learning materials, observation and collaboration between teachers, access to educational resources, recognition, and appreciation, as well as supervision and feedback. In this context, principal leadership played an important role in facilitating the implementation of these strategies, ensuring their effective implementation, and creating an environment that supported the development of teacher pedagogical competencies.